Empowering STEAM Education Through Survival Reality Show: A Literature Review of ‘University War’ to Enhance Problem Solving Skills in Physics Learning - Bilqisth Dwi Athiah; Wasis; Noval Hulu (Journal of Digitalization in Physics Education, 2025)
Objective: This study intends to analyze the enhancement of problem-solving abilities through the survival reality program 'University War' in high school physics learning and to characterize the empowerment of STEAM education. Methods: This study employs a library research approach. Thirty-two journal articles were evaluated to collect secondary data, which was obtained through the evaluation of research journals from various online journal sources. Results: Of the papers that were evaluated, one survival reality show and eighteen essays from 2020 to 2024 addressed the matter in question. The findings and analysis of secondary data, demonstrating how STEAM education is strengthened through the survival reality show 'University War' in physics learning at the high school level, are very suitable for applying to improve problem-solving skills. Novelty: In addition to improving problem-solving skills, STEAM empowerment through the TV program can increase student motivation. The challenges in the program are suitable for students to improve their problem-solving skills and also provide a non-monotonous classroom atmosphere.